Verification of a DDA-based hydro-mechanical model and its application to dam foundation stability analysis. (February 2021) - Zhang, Qi-Hua; Shi, Gen-Hua
Abstract: There are many studies concerning hydro-mechanical coupling model based on discontinuous deformation analysis (DDA). However, verification of the coupling model and its application to practical engineering are rarely found. In this paper, we first introduced the distributed load sub-matrix of water pressure and described the calculation procedures of hydro-mechanical coupling analysis in the framework of DDA. Then, the correctness of the coupling model was verified respectively through analyses of buoyancy, deformation of a block under uniform water pressure and hydraulic fracturing. Finally, the model was applied to evaluate the sliding stability of a gravity dam foundation in China. The failure process and stability factor were calculated by two different stability evaluation methods (the strength reduction method and the overloading method), and the obtained stability factors were compared with those solved by the commonly used limit equilibrium analysis methods. The strength reduction method revealed that the rock strata of dam foundation slide with different displacements along several weak interlayers of different depths, whereas the overloading method revealed that the rock strata slide mainly along a special interlayer beneath the anti-sliding concrete stud, which was designed to be near the dam heel. The DDA method clearly shows the process of rock block failure and profoundly reveals the difference in sliding mode caused by using different stability evaluation methods.